Vpliv epidemije covida-19 na življenje stanovalcev domov za stare - Štrancar, Anže (Socialno delo, 2022)
The year 2020 was marked by the Covid-19 epidemic, which had the greatest impact on socially vulnerable groups, especially old people. Based on qualitative research, the article explains the impact of measures to curb the Covid-19 epidemic on the lives of old people in the Ajdovščina Home for the Old People. During this period, social work found itself in a difficult situation and was forced to respond. In institutions for old people, it found itself in an unenviable position, as it had to adapt very quickly to new challenges - to maintain contact in a time that severely limited physical contact, and to enable communication between residents and their loved ones. The article connects homes for old people with the concept of a total institution and shows how social work in the home for old people coped with challenges during the Covid-19 epidemic. The impact of epidemiological measures and social isolation on people's mental health and everyday life is shown. The fundamental tasks of social workers in crisis situations are listed.
Keywords: duševno zdravje; institucionalisation; institucionalizacija; mental health; old people; social isolation; social work; socialna izolacija; socialno delo; stari ljudje